Effects and evaluation of biogas slurry/water integrated irrigation technology on the growth, yield and quality of tomatoes - Zheng, Jian; Qi, Xingyun; Yang, Shaohong; Shi, Cong; Feng, Zhengjiang (International Journal of Agricultural and Biological Engineering, 2022)
Reasonable techniques and methods in biogas slurry application are significant for the promotion of biogas slurry and the improvement of crop quality in agricultural production. To investigate the impacts of different biogas slurry application techniques on the water use efficiency, growth, yield, and quality of tomatoes, three irrigation techniques, and two application methods were considered in this study. The three irrigation techniques are alternate partial root-zone irrigation (APRI), fixed partial root-zone irrigation (FPRI), and two sides root-zone irrigation (TSRI). Two application methods refer to applying the biogas slurry with hole irrigation and surface irrigation. In addition, principal component analysis (PCA) and technique for order preference by similarity to ideal solution (TOPSIS) methods were adopted to evaluate the comprehensive quality and comprehensive indicators of tomatoes among different treatments. There are three hole irrigation treatments, T1 (APRI), T2 (TSRI), T3 (FPRI), and three surface irrigation treatments, T4 (APRI), T5 (TSRI), and T6 (FPRI) were set in two-season pot experiments. The results show that the plant height, dry matter accumulation, fruit yield, and water use efficiency present a similar descending trend for APRI, TSRI, and FPRI under the same methane irrigation method, yet show that the hole irrigation treatment was higher than the surface irrigation treatment for the same irrigation technique. These indicate that the coupling of APRI technique and hole irrigation is more conducive to the increase of plant production and water use efficiency. Meanwhile, T1 treatment can significantly improve the soluble sugar, sugar-acid ratio, VC content, soluble protein, soluble solid content, and firmness of tomato fruits, which are better for the taste, storage, and transportation of tomato fruit. The titratable acid content in tomato fruit is the highest in T2 treatment, followed by T5 treatment, indicating that TSRI technique may result in an accumulation of titratable acid and is not conducive to the taste of the tomato. The comprehensive nutritional quality and index evaluation results show that T1 treatment ranks the highest among all treatments, and can be used as an optimal irrigation method for the implementation of integrated water/biogas slurry.Keywords: biogas slurry, irrigation technique, coupling, quality evaluation, comprehensive index evaluationDOI: 10.25165/j.ijabe.20221505.6901Citation: Zheng J, Qi X Y, Yang S H, Shi C, Feng Z J. Effects and evaluation of biogas slurry/water integrated irrigation technology on the growth, yield and quality of tomatoes. Int J Agric & Biol Eng, 2022; 15(5): 123–131.